Paths beyond Petrópolis: from the royal roads to the highways - Martins , Thaissa; Barcellos, Fernanda; Drach , Patricia (Technical and Scientific Journal Green Cities, 2022)
The difficulties in crossing the great wall of almost 1,000m and accessing the “Serra da Estrela” mountain range meant that, during the first 200 years of Portuguese colonisation, the Atlantic Forest region remained practically untouched and protected. In order to enter the territory and reach the region of Minas Gerais, this shorter, but steep access, where river crossings were impossible during rainy seasons, was replaced by longer, but safer ones. The roads cut through the region coming from the city of Paraty and reaching the gold production region through a network of paths. In this work, the initial access and the ways that led to the city of Petrópolis were mapped, from the old the old Emperor’s path, part of the “Royal Roads”, to the current highways. Some of the industries of the city, whose location on maps allows us to relate their presence to the arrival of the railway, and then the roads, are presented here. Considering the city’s location among valleys and along rivers, which enabled the existence of several accesses, it is interesting to observe that it does not have a proper industrial region, but small sites along the roads that correspond to the interests of specific historical moments. A synthesis graphic presenting the association of the mapped data was generated, providing a general scenario of the location of some industries over time, from the foundational site, establishing its relationship with the opening of new paths and the city’s expansion. KEYWORDS: Petrópolis; railways; highways; industries.